Records of real people linguistic variation in Middle English local documents - Stenroos, Merja-Riitta; Thengs, Kjetil V. (Advances in historical sociolinguistics ;, 2020)
"English local documents - leases, wills, accounts, letters and the like - provide a unique resource for historical sociolinguistics. Abundant from the early fifteenth century, they represent the language and concerns of people from a wide range of social, institutional and geographical backgrounds. However, as relatively few documents have been available digitally or in print, they have been an underresearched resource. This volume shows the tremendous potential of late- and post-medieval English local documents: highly variable in language, often colourful, including developing formulae as well as glimpses of actual recorded speech. The volume contains eleven chapters relating to a new resource, A Corpus of Middle English Local Documents (MELD). The first four chapters outline a theoretical and methodological approach to the study of local documents. The remaining seven present studies of different aspects of the material, including supralocalization, local patterns of spelling and morphology, land terminology, punctuation, formulaicness and multilingualism"--